Generation of infectious disease alerts through the use of geolocation - Antonio Sarasa Cabezuelo (Institute of Advanced Engineering and Science, 2020)
In recent years, there have been several cases of global epidemics such as influenza B or Ebola. In these cases, several factors are key to limit the effects of the epidemic and avoid contagion. Between of them is the speed of knowing which persons are infected, which persons has been in contact with any infected person or know what the focus of the epidemic. In general, obtaining this information requires a process of research among the first affected that can be slow and complicated. This article describes a tool that aims to generate alerts when there are data about an epidemic, and notify all persons who could be exposed to contagion and prevent new infections occurs.